2006
DOI: 10.4049/jimmunol.176.12.7431
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Particle-Exposed Human Bronchial Epithelial Cells Induce Dendritic Cell Maturation

Abstract: Increased exposure to air pollutants such as diesel exhaust particles (DEP) has been proposed as one mechanism to explain the rise in allergic disorders. However, the immunologic mechanisms by which DEP enhance allergic sensitization and asthma remain unclear. We hypothesized that DEP act as an adjuvant for immature dendritic cell (DC) maturation via its effect on airway epithelial cell-derived microenvironment for DC. Immature monocyte-derived DC (iMDDC) failed to undergo phenotypic (CD80, CD83, CD86) or func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
110
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 49 publications
7
110
2
1
Order By: Relevance
“…That such an effect is enhanced with GM‐CSF is in agreement with our current understanding for a pro‐inflammatory role for GM‐CSF in pollution‐induced lung disease 16, 18, 19. Although not the focus of this research, our finding of suppression of MHC class I expression by GM‐CSF is intriguing and deserves more detailed investigation in dedicated studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…That such an effect is enhanced with GM‐CSF is in agreement with our current understanding for a pro‐inflammatory role for GM‐CSF in pollution‐induced lung disease 16, 18, 19. Although not the focus of this research, our finding of suppression of MHC class I expression by GM‐CSF is intriguing and deserves more detailed investigation in dedicated studies.…”
Section: Discussionsupporting
confidence: 89%
“…GM‐CSF is important for survival of DCs in non‐lymphoid tissue,25 and the action of GM‐CSF on pulmonary DCs is influential in lymphocyte responses in the lung 25, 26. Treatment of epithelial cells with diesel exhaust particles, a major component of UPM, is known to stimulate production of GM‐CSF that in turn promotes DC maturation and activation 18. It is therefore pertinent to consider the actions of UPM on CD8 priming in the context of the GM‐CSF‐rich pulmonary environment.…”
Section: Introductionmentioning
confidence: 99%
“…It seems likely therefore that DC will be among the first cells to sense and respond to inhaled PM, although the importance of bronchial/pulmonary epithelial cells cannot be overlooked. It is possible that exposure to PM disrupts the integrity of pulmonary epithelial cells and thereby releases inflammatory cytokines that activate DC and drive Th2-mediated allergic immunity as suggested by others [57,58] . An attractive mechanism responsible for DC activation by epithelial cells suggests release of granulocyte-macrophage colony-stimulating factor and thymic stromal lymphopoietin (TSLP) on exposure to particulate pollutants that may also involve oxidative stress and the generation of reactive oxygen species in the activation of pulmonary DC [11,42,54,57,59] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that epithelial cells in the gastric mucosa condition local DCs through the release of soluble mediators, resulting in a noninflammatory phenotype that is crucial for the maintenance of intestinal homeostasis (23). More recent studies of the lung microenvironment suggest that AECs may also condition fully differentiated DCs (24,25). However, there is no information available that relates specifically to the situation prevailing in conducting airway tissues, i.e., where incoming monocytes recruited by inflammatory stimuli undergo maturation into DCs within the epithelium itself.…”
mentioning
confidence: 99%